ION Flux–Film Structure Realtionship During Reactive Magnetron Sputtering of Tungsten - Hemberg, Axel; Konstantinidis, Stephanos; Dauchot, Jean-pierre; Snyder, Ryne (International Conference on Plasma Surface Engineering, 2013)
Not available